O projeto temático na sala de aula: mudanças nas interações discursivas - Penha das Dores Souza Silva (2009)
In the present work we investigate how a thematic project Water in Focus: Life Quality and Citizenship changed the dynamic of chemistry classes in a 1th Grade High School, in a public school in Minas Gerais state. This work is situated in the fields of Historical-Cultural Perspective and Bakhtins Enunciation Theory. The methodological procedures included the application of a questionnaire, recordings of classes and interviews. Were realized recordings of two classroom sequences of a teacher that contributed to this research. The classes of the first sequence, which we call set 1, were filmed during a regular class and the classes of the second sequence, which we call set 2, referring to classes in which the Project Water in Focus were developed. To answer the proposed questions, we establish as research resource, the contrast between enunciating strategies in both sequences. The interview with the teacher gave us clear aspects of his/her practice, which cannot be perceived by video data. The analysis of maps events and discursive sequences revealed that several strategies suggested by the project, such as: group activities, practical activities and question resolution after completion of practical activities, were used during the teacher classes, supporting the realization of more interactive, and dialogical classes in set 2, when compared with set 1. Considering the classes analysis, is possible to affirm that the methodology used allowed the characterization, with greater detailing, of the discursive dynamics adopted in teaching, favoring the contrast and perception of differences and similarities between the two sets